Accelerated ageing test to evaluate seed vigor in pumpkin and zucchini seeds - Dutra, A. S.; Vieira, Roberval Daiton [UNESP] (Ista-int Seed Testing Assoc, 2006)
The accelerated ageing (AA) test is widely used to evaluate seed vigor in various species including vegetable crops. The objective of this work was to study procedures for conducting AA to evaluate seed vigor of pumpkin and zucchini seed lots. Five seed lots of commercially acceptable quality (germination) standards were selected from both cv. `Menina Brasileira' (zucchini) and `Barbara' Hybrid (pumpkin). The following tests were conducted: standard germination, the first count of germination, and AA with and without saline solution (periods of 48, 72 and 96 hours). For each combination of temperature and ageing period, seeds were placed in a single layer on a screen in a germination plastic box with either 40 mL deionized water or 40g NaCl/100mL of water. Both AA methods identified lots 2 and 5 of `Menina Brasileira' and lot 10 of `Barbara' hybrid as having the lowest physiological quality. The temperature 41 C promoted a more drastic reduction in germination than did 38 C. This observation was more marked after 96 hours. Based on the results obtained, it can be concluded that the combination 41 degrees C/96 hours should be used to evaluate the physiological potential of pumpkin and zucchini seeds; however, additional studies are necessary to evaluate other combinations and confirm this indication.